2015
DOI: 10.1590/s0036-46652015000300011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin C Supplementation on the Chronic Phase of Chagas Disease

Abstract: Introduction:In order to examine the effectiveness of vitamin C (ascorbic acid) in combating the oxidative insult caused by Trypanosoma cruzi during the development of the chronic phase of Chagas disease, Swiss mice were infected intraperitoneally with 5.0 × 104 trypomastigotes of T. cruzi QM1strain.Methods:Mice were given supplements of two different doses of vitamin C for 180 days. Levels of lipid oxidation (as indicated by thiobarbituric acid reactive substances-TBARS), total peroxide, vitamin C, and reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
7
0
2
Order By: Relevance
“…The use of nutritional supplements to aid in host response against protozoan parasites has been studied, some of which revealed anti-trypanosome effects. Ascorbic acid (vitamin C) has been shown to aid in combating the oxidative stress injuries in vital organs of mice infected with Trypanosoma cruzi [ 9 ]. Epigallocatechin gallate (an analog of green tea extract) administration to mice showed significant levels of decreased parasitism and increased survival rates suggesting that epigallocatechin gallate may be potentially useful for the protection against T. cruzi [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of nutritional supplements to aid in host response against protozoan parasites has been studied, some of which revealed anti-trypanosome effects. Ascorbic acid (vitamin C) has been shown to aid in combating the oxidative stress injuries in vital organs of mice infected with Trypanosoma cruzi [ 9 ]. Epigallocatechin gallate (an analog of green tea extract) administration to mice showed significant levels of decreased parasitism and increased survival rates suggesting that epigallocatechin gallate may be potentially useful for the protection against T. cruzi [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In light of this finding, it may be postulated that in our study due to intoxication with high dose of ParCM in group D, the activity of heme oxygenase might have accelerated resulting in frequent availability of free transition iron and presence of AsAc, causing reduction of transition metal ions, boost of the Fenton reaction, and detrimental effects on the liver cells. Wang et al (2007), Park and Lee (2008), Kamel et al (2010), and Marim et al (2015) have all reported the damaging effects of AsAc in their studies (Kamel et al, 2010;Marim et al, 2015;Park and Lee, 2008;Wang et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…in Chagas mice, though this seemed to be a dose-dependent effect; treatment with 60 mg vitC was not oxidative, while treatment with 500 mg of vitC per day led to increased total peroxide and TBARS at 60 and 180 days [52,60].…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 90%